THE MONODISCIPLINARY APPROACH IN KNOWLEDGE DEVELOPMENT AND ITS IMPLICATIONS FOR KNOWLEDGE INTEGRATION - Fara Fariha Rodliyana; Samas Muizul Mala (International Journal of Multidisciplinary Reseach, 2026)
This study explores the monodisciplinary approach in the development of Islamic Education Management (MPI) as an epistemic foundation to strengthen the identity, structure, and scientific orientation of the discipline. The research aims to analyze the urgency of adopting a monodisciplinary approach within MPI studies and to evaluate its contribution to reinforcing fundamental concepts and theoretical frameworks before moving toward cross-disciplinary integration. The method employed is a library research approach with descriptive qualitative analysis by reviewing various academic sources related to monodisciplinary development, Islamic epistemology, and the contextualization of MPI. The findings indicate that monodisciplinarity plays a pivotal role in enhancing specialization, clarifying conceptual frameworks, and establishing methodological legitimacy for MPI as an autonomous and scientifically accountable discipline. Nevertheless, the study also reveals that a dominant reliance on a purely monodisciplinary approach may lead to fragmented knowledge and limited capacity in addressing the complexity of contemporary educational challenges. Therefore, this approach should be positioned as an initial and progressive stage toward more comprehensive interconnection and integration of knowledge. Overall, the monodisciplinary approach remains a necessary foundation in the development of MPI; however, its implementation must be adaptive and open to dialogue with contemporary management perspectives, Islamic values, and the global dynamics of education.